Causes, consequences, and cures of myopic loss aversion: An experimental investigation - Gerlinde Fellner; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2008)
We examine in an experiment the causes, consequences and possible cures of myopic loss aversion (MLA) for investment behaviour under risk. We find that both, investment horizons and feedback frequency contribute almost equally to the effects of MLA. Longer investment horizons and less frequent feedback lead to higher investments. However, when given the choice, subjects prefer on average shorter investment horizons and more frequent feedback. Exploiting the status quo bias by setting a long investment horizon or low feedback frequency as a default turns out to be a successful behavioural intervention that increases investment levels.
Keywords: C91; D80; G11; 330; myopic loss aversion; risk; investment; experiment; Anlageverhalten; Risikoaversion; Test; Informationsverhalten; Equity Premium Puzzle; Theorie